2022
DOI: 10.3390/biom12050660
|View full text |Cite
|
Sign up to set email alerts
|

Silk Fibroin-Based Biomaterials for Hemostatic Applications

Abstract: Hemostasis plays an essential role in all surgical procedures. Uncontrolled hemorrhage is the primary cause of death during surgeries, and effective blood loss control can significantly reduce mortality. For modern surgeons to select the right agent at the right time, they must understand the mechanisms of action, the effectiveness, and the possible adverse effects of each agent. Over the past decade, various hemostatic agents have grown intensely. These agents vary from absorbable topical hemostats, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 90 publications
(120 reference statements)
1
15
0
Order By: Relevance
“…The R time of this experiment would not be directly interpreted as aPTT due to the difference between measuring instruments and methods. Still, it could indicate the degree of intrinsic pathway activation like other clotting time tests targeted the intrinsic pathway with TEG. , Therefore, this result is consistent with previous studies that determined that aPTT decreased with increasing SF. , The intrinsic pathway is initiated by the clotting factor (FXII), a zymogen present in blood plasma, binding to external surfaces other than the inner blood vessel wall . Since the active site of FXII mainly contains positively charged amino acids, it likely binds to the negatively charged surface .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The R time of this experiment would not be directly interpreted as aPTT due to the difference between measuring instruments and methods. Still, it could indicate the degree of intrinsic pathway activation like other clotting time tests targeted the intrinsic pathway with TEG. , Therefore, this result is consistent with previous studies that determined that aPTT decreased with increasing SF. , The intrinsic pathway is initiated by the clotting factor (FXII), a zymogen present in blood plasma, binding to external surfaces other than the inner blood vessel wall . Since the active site of FXII mainly contains positively charged amino acids, it likely binds to the negatively charged surface .…”
Section: Resultssupporting
confidence: 88%
“…The intrinsic pathway is also inferred to be induced by negatively charged SF . Therefore, it is assumed that the SF component of the sponge affect the physiological hemostasis process. , However, natural hemostasis is not the only factor determining blood coagulation. As the ratio of starch increased, the blood clotting ability of SF/ST sponges quantified by BCI was improved.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, although some studies have reported the hemostatic effect of the SF, in most cases it was combined with other components, so it is difficult to figure out the effectiveness of the SF itself. Therefore, the thorough hemostatic mechanism of the SF still needs to be comprehensively explored [ 13 , 98 ]. Keratin-based Material …”
Section: Molecular Structure Design Of the Hemostasis Materialsmentioning
confidence: 99%
“…Even with the same component, hemostatic materials can be prepared into different forms, e.g., powder, sponge, gauze and hydrogel, which endowed them with different hemostatic mechanisms [ 13 ]. Under different circumstances (bleeding site, depth, environment, etc), such materials have shown particular advantages for hemostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Silk fibroin (SF) is a natural polymer produced from the silkworm Bombyx mori , which was approved for use as a biomaterial in 1993 by the FDA. Recently, it has been extensively applied in the tissue engineering and biomedical fields owing to its exceptional biocompatibility, flexible mechanical properties, controlled biodegradation, and minimal propensity to invoke immune reactions [ 32 , 33 , 34 ]. SF comprises a repetition of Gly–Ala–Gly–Ala–Gly–Ser repeats of amino acid sequences, forming a β-sheet structure by self-assembly [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%